Biological markers of exposure to organophosphorus nerve agents - Black, Robin M.; Read, Robert W. (Archives of toxicology, 2013)
Organophosphorus nerve agents are the most toxic chemical warfare agents that are known to have been produced, stockpiled and weaponised. Their development, production, stockpiling and use are prohibited under the terms of the Chemical Weapons Convention and, together with their precursors, are subject to strict controls and verification procedures. The detection and identification of biological markers of exposure to nerve agents are required for three main purposes: confirmation of exposure for forensic purposes in cases of alleged use; diagnosis to guide appropriate medical countermeasures in the event of an exposure; and occupational health monitoring of workers in defence laboratories and demilitarisation facilities. Biomarkers of nerve agents fall into two main groups, free metabolites and adducts to proteins. These are reviewed together with analytical methods for their identification. Examples are provided of applications in cases of human exposure.